2019
DOI: 10.2478/amcs-2019-0038
|View full text |Cite
|
Sign up to set email alerts
|

A Reference Trajectory Based Discrete Time Sliding Mode Control Strategy

Abstract: This study presents a new, reference trajectory based sliding mode control strategy for disturbed discrete time dynamical systems. The desired trajectory, which is generated externally according to an existing switching type reaching law, determines the properties of the emerging sliding motion of the system. It is proved that an appropriate choice of the trajectory generator parameters ensures the existence of the quasi-sliding motion of the system according to the definition by Gao et al. (1995) in spite of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…It is observed that the switching function is affected by all the disturbance terms, i.e., d(0), d(1), ..., in the whole control process. The idea of the reference trajectory generator was first presented in [18,[23][24][25] and then introduced in this method, where the switching function s(k + 1) is regulated with the guidance of the desired trajectory s d (k). It is noted that s d (k) is not influenced by the disturbance.…”
Section: Proposed Methodsmentioning
confidence: 99%
“…It is observed that the switching function is affected by all the disturbance terms, i.e., d(0), d(1), ..., in the whole control process. The idea of the reference trajectory generator was first presented in [18,[23][24][25] and then introduced in this method, where the switching function s(k + 1) is regulated with the guidance of the desired trajectory s d (k). It is noted that s d (k) is not influenced by the disturbance.…”
Section: Proposed Methodsmentioning
confidence: 99%
“…To avoid this inefficiency, new approaches have been proposed to improve the POD-Galerkin method for nonlinear systems. These approaches include the trajectory piecewise-linear (TPWL) method (Rewieński, 2003;Rewienski and White, 2006), a reference trajectory based mode control strategy for discrete time dynamical system (Bartoszewicz and Adamiak, 2019), a heuristic algorithm based on linear matrix inequalities (LMIs) (Sanjuan et al, 2019), missing point estimation (MPE) (Astrid, 2004), and discrete empirical interpolation (DEIM) (Chaturantabut and Sorensen, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, one of the promising approaches to fault detection and identification is the use of the observers operating in a sliding mode (Utkin, 1992) (sliding mode observers, SOs). Nowadays, the SOs are applied to solve the problems of fault identification in linear (Edwards and Spurgeon, 1994;Fridman et al, 2007;Edwards et al, 2000) and nonlinear (Davila et al, 2006;He and Zhang, 2012;Rascón et al, 2017) systems, to ensure fault-tolerant control (Edwards et al, 2012;Alwi and Edwards, 2008;Bartoszewicz and Adamiak, 2019).…”
Section: Introductionmentioning
confidence: 99%